THE SOCIAL NETWORK AFFILIATES AGAINST AT NEED YOUNG PEOPLE OF THE FACULTY OF PSYCHOLOGY UIN RADEN FATAH PALEMBANG - Fathur rahman, Ahmad cakra Aulia; Susilo, Muhammad Rizky Sahputhra; oktavia, Hania; Insyra, Attalah Rahma; livia, Trisna; akbar, Muhammad bilal (Indonesian Journal of Multidisciplinary Sciences (IJoMS), 2022)
One of the human needs is to interact with the people around him. Social interaction is a dynamic social relationship to build social relationships. Adolescence is a period of developmental transition towards adulthood, involving biological, cognitive and social changes. The urge to affiliate appears as well as with adolescents because as social beings they have various kinds of needs that must be met. Various means of communication that can be used in interaction, a means of communication that is currently a trend among adolescents is communication using social networks. This study aims to determine the effect of social networking on the needs of adolescent clients in the Islamic Psychology Study Program, Faculty of Psychology, Raden Fatah State Islamic University. This research is a quantitative study with a sample of 34 adolescents aged 18-21 years who come from students of the Islamic Psychology Study Program, Faculty of Psychology, Raden Fatah State Islamic University. The sampling technique used is random sampling. The independent variable in this study is social networking, while the dependent variable is the need for affiliation. The method of analysis of the data used is the method = 0,339 scale with the r , p & 0,05; gt .The research through kusioner propagated in 34 respondents .5 % significant: 0,05 5 .Obtained 0,339 table of r .From the data r table smaller than on the validity of the data .This suggests that social networking is influencing the affiliation student Uin Raden Fatah Palembang the 2020